The Application of Yellow Book Learning in Increasing the Knowledge of Students in At-Taroqqi Karongan Sampang Islamic Boarding School - Fatoni, Ach.; El-Yunusi, Muhammad Yusron Maulana (Civiliza Publishing, 2024)
This study aims to examine the application of yellow book learning in improving the knowledge of students at the At-Taroqqi Islamic Boarding School, Karongan, Sampang. Yellow book is a classic book that is the main reference source in traditional Islamic religious education in Indonesian Islamic boarding schools, especially in understanding religious sciences such as fiqh, tafsir, and hadith. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. Participants in this study were students and teachers involved in learning yellow books at PP. At-Taroqqi. The results of the study indicate that the application of the yellow book learning method can effectively improve students' understanding and knowledge of Islamic teachings and build strong religious character. In addition, the contextual approach and the sorogan and bandongan methods applied are able to encourage active involvement of students in the learning process. This finding emphasizes the importance of preserving yellow book learning as a teaching medium that not only focuses on cognitive aspects, but also forms students' morals and personalities.